Pseudo Janus based on rhombohedral homobilayer transition metal dichalcogenides. Issue 31 (26th July 2022) - Lin, Changqing; Xiang, Hui; Xiong, Heqi; Ahmad, Sohail; Xu, Bo; Zhao, Puqin; Cheng, Yingchun
Abstract : Out-of-plane mirror symmetry breaking has enabled pseudo Janus structures as a platform to explore the coupling between electric polarization, piezoelectricity, spin–orbit coupling, and Rashba splitting in a two-dimensional (2D) system. Abstract : Out-of-plane mirror symmetry breaking has enabled monolayer Janus structures as a platform to explore the coupling between electric polarization and the lattice, spin–orbit coupling, or magnetism in a two-dimensional (2D) system. However, the difficulties of synthesis hinder the experimental exploration of predicted multi-properties and potential applications based on monolayer Janus structures. Because of inversion symmetry breaking, rhombohedral (3R) homobilayer transition metal dichalcogenides (TMDCs) show intrinsic out-of-plane electric polarization. Here, we take a 3R stacking TMDC, which can be grown/fabricated directly by chemical vapor deposition or dry transfer as a representative and study the charge, spin and valley degrees of freedom. 3R homobilayer TMDCs has an out-of-plane electric polarization, piezoelectricity, and giant Rashba effect, which is similar to monolayer Janus TMDCs. Therefore, we propose a 3R homobilayer 2D material as a pseudo Janus structure. In addition, the 3R homobilayer TMDC presents a spin-dipole locking effect, which is beyond monolayer Janus TMDCs. Our study broadens the family of Janus materials while highlighting stacking as a new degree to tailor the properties of 2D materials.